Penyalahgunaan Ciri-ciri Ragawi oleh Rasisma - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Racial discrimination is usually elicited by social, economic, religious or political reasons, and then justified by quasi-scientific arguments, c. q. by using anatomical and anthropological data.Almost all parts of the body have been used to justify racial discrimination, particularly easily visible physical traits. Not infrequently data are unhesitantly manipulated•in order to arrive at conclusions in tune with racist ideas nurtured. Physical traits are purposefully correlated with mental and behavioural traits to give a negative image of the race disliked.The progress of science seems to be not proportional to the decrease in racial discrimination. The number of anthropologists and the history of anthropology in a country do not influence the extent of racial discrimination. Scientific data will always be used for pragmatic ends in. intergroup socioeconomic competition. 'To abolish or substitute the term race or the race concept will not ne• cessarily abolish racial discrimination. It is hoped that in the future groups which have experienced discrimination will not resort to retaliation and use the same methods, even if the biological concept of race is maintained.Key Words: racism -- human races -- miscegenation - racial characteristics - heterosis